Contextual Character Education Strategies at Home to Foster Discipline and Empathy In Children - Rilawati, Jelsy Anjelina; Nur Hidayat; Anisaturrahmi (PGMI IAIN Lhokseumawe, 2025)
Character education plays an important role in shaping children's personalities so that they are not only academically better, but also have a disciplined and empathetic attitude. The home environment, namely parents, is the main foundation in the process of internalizing moral values through role modeling, habituation, and daily interactions. However, the implementation of character education at home still faces various obstacles, such as a lack of role models, a lack of understanding of parenting, and the influence of digital challenges. This study aims to examine and formulate contextual character education strategies at home to foster discipline and empathy in children. This study used the Systematic Literature Review (SLR) method by searching for scientific articles, books, and research reports through Google Scholar, SINTA, DOAJ, and university portals from 2015 to 2025. Data analysis used thematic analysis techniques with stages of literature identification, selection, quality evaluation, and theme classification. The results of the study show that effective contextual strategies include habituation, the 5S culture (Smile, Greet, Say Hello, Be Polite, Be Courteous), parental role modeling, responsive parenting, strengthening religious values, shared literacy, and moral communication. These strategies can strengthen children's discipline and foster empathy through the formation of prosocial behavior, understanding of other people's feelings, and consistency in carrying out positive activities within the family environment. Thus, family-based character education needs to be designed in a contextual, consistent, and sustainable manner in order to optimally shape disciplined and empathetic character